2020
DOI: 10.1038/s41598-020-57636-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of proton pump inhibitor partial response in gastroesophageal reflux disease in systemic sclerosis: a prospective study

Abstract: Proton pump inhibitor (PPI) twice daily dosing is a standard therapy for gastroesophageal reflux disease (GeRD) in systemic sclerosis (SSc) but there is no data on its response rate or the predictors of ppipartial response GeRD. Aims were to determine the prevalence of ppi-partial response GeRD in SSc and to define its predictors. A prospective study was conducted in SSc patients with GERD. The patients were treated with omeprazole 20 mg bid for 4 weeks. The severity of symptom-grading by visual analogue scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…The results of our Delphi study showed that, according to the panellists, most SSc-ILD patients suffer from a number of comorbidities, such as gastroesophageal reflux disease (53.8%), fatigue (40.3%) or depression (22.6%). These results are consistent with the reports in the literature for SSc or SSc-ILD patients [ 32 – 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of our Delphi study showed that, according to the panellists, most SSc-ILD patients suffer from a number of comorbidities, such as gastroesophageal reflux disease (53.8%), fatigue (40.3%) or depression (22.6%). These results are consistent with the reports in the literature for SSc or SSc-ILD patients [ 32 – 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The existence of delayed emptying of stomach may result in an insufficient response to treatment in these patients. In addition, Ren LH et al meta-analysis in 2016, showed that therapy of combination with prokinetics and PPIs improved the individual life quality by reducing the episodes of acid reflux episodes 20 . In this study, the mean score of FSSG was moderately in height (17.20 ± 8.40).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic approaches based on PPIs and prokinetic medications effectively reduce GERD manifestations while improving gastric emptying, esophageal sphincter pressure, and intestinal peristalsis. [50][51][52] Endoscopic dilatation and continuous administration are preferred therapies for systematically managing and preventing esophageal strictures in systemic sclerosis. EGD surveillance with biopsy is recommended in Barrett's esophagus, and treatment includes endoscopic ablation or resection of dysplastic epithelium using photochemical, thermal, or radio ablation energy.…”
Section: Esophagusmentioning
confidence: 99%